OUTCOMES OF PEOPLE LIVING WITH HIV IN TWO PUBLIC-SECTOR PSYCHIATRIC FACILITIES IN THE EASTERN CAPE USING EFAVIRENZ-CONTAINING REGIMENS - Gaida, Razia; Truter, Ilse; Grobler, Christoffel (African Journal of Infectious Diseases (AJID), 2020)
Background: People with mental disorders are more vulnerable to human immunodeficiency virus (HIV) infection. Although part of first-line treatment for HIV, efavirenz is routinely avoided in patients with mental illness due to the risk of potentially aggravating the mental illness. The study aimed to determine the outcomes of people living with HIV/AIDS who were mental healthcare users admitted to a public-sector psychiatric facility prescribed an efavirenz-containing regimen. Materials and Methods: A prospective drug utilization study was conducted at two public-sector psychiatric hospitals in the Eastern Cape, South Africa. Patients aged 18 years or older and living with HIV were included in the study. Follow-up reviews were conducted at four, 12 and 24 weeks. The patients were seen by doctors at the hospital and notes on progress and medication were recorded in medical records. These files were reviewed. Results: A total of 37 patients were enrolled however, just 26 were reviewed at 24 weeks. A total of 43.2% (n=16) were female patients and the average age of the patients was 39.38±8.76 years. At baseline, 32.4% (n=12) patients were diagnosed with schizophrenia. A total of 81.08% (n=30) of patients experienced an improvement in psychiatric symptoms after 24 weeks. Of these, 43.3% (n=13) were on an efavirenz-containing regimen. Conclusion: The majority of patients demonstrated an improvement in their psychiatric condition to the extent that they were discharged into the community. Half were using an efavirenz-containing regimen. This indicates that patients with psychiatric disorders on efavirenz can experience stabilisation of their psychiatric symptoms.